Permasalahan Sosial Pada Masyarakat - Tutesa; Yossita Wisman (Jurnal Pendidikan Ilmu Pengetahuan Sosial (JPIPS), 2020)
Social inequality is a state of social imbalance in society that makes a very striking difference. In terms of social inequality, it is very clear from various aspects, for example in the aspect of justice it can occur. Between rich and poor people are very differentiated in any aspect, villagers who migrate to the city are also affected by this, it is true to say that "The rich will be rich, the poor will get poorer". This indifference to others is due to the overly averse gap between the "rich" and the "poor". Many rich people look down on the lower class, especially if they are poor and dirty, let alone helping, they are just ignorant. While there are many street children who do not have a place to live and sleep on the streets, but there are still many people who are lazy to sleep in star hotels, there are many people out there who are starving and cannot feed their children but there are more rich people. being engrossed in eating a variety of delicious food at exorbitant prices. While many poor people are cold because of clothes that they don't fit to wear, many rich people who are rich buy clothes, and sometimes even order clothes from designers for 250,000 million, with that much price it should be able to feed the poor. the hungry.